Analysis of Erosion Rate on Discharge Slurry HDPE Pipe in Canal Water Intake PLTGU Grati using CFD Simulation - Agoes Santoso; Bahrul Ilmi (International Journal of Marine Engineering Innovation and Research, 2018)
The dredging of the canal water intake at PLTGU Grati is an effort to maintain the depth of the reduced canal due to sedimentation. The dredging process itself uses a cutter suction dredger. To distribute mud or slurry (a mixture of water and sand) result of dredging to dumping area of  PLTGU Grati using HDPE (high-density polyethylene), as pipe material, hence pipe does not wear due to corrosion but erosion. Basically, erosion is caused by impact of solid particle (sand) which is suspended inflow (multiphase) on a solid wall boundary. Wear caused by erosion itself is recognized as one of the problems in some industries that distribute slurry in their process. This research thesis analyzes and predicts the rate of erosion occurring in HDPE pipes that are transported slurry from the sedimentation dredging in PLTGU Grati using CFD (computational fluid dynamic) method. Variations of slurry concentration, impact angle, particle diameter and velocity of the slurry has been be performed to determine the effect on the rate of erosion. The results of this research thesis showed that the concentration of slurry, impact angel, diameter of particle and the concentration of the slurry were directly proportional to the rate of erosion on the HDPE pipe.